PKM PENINGKATAN KOMPETENSI SISWA SMK ABDI NEGARA MELALUI PELATIHAN MACRO UNTUK PEMBUATAN APLIKASI AKUNTANSI SEDERHANA - R.S. Samosir; M. Rusli; Erwin Syahrani (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2019)
PKM For SMK Abdi Negara 2 Cibarusah with Accounting and Office Administration Majoring is done to solve the problem faced by them. As a prospective graduate who will have a considerable opportunity to become an admin and secretary for a company, the prospective graduates need to be equipped with knowledge and expertise in the use of computer technology. One of the most widely used computer technologies in office administration is Microsoft Excel. Knowledge and expertise in utilizing Microsoft Excel are currently quite good but they still have this problem in using this device. The problem is how to use the Macro features in microsot excel to help them create a simple accounting application. The solution offered is by training the vocational students and students for two days. The purpose of this training is to increase students' knowledge and expertise in preparing the world of work. The results of this training were to increase the knowledge and expertise of students in accounting and office administration major.